Decent Housing Rights Handling Related to Backlog During Covid-19 Pandemic: Samarinda City Case Study - Asnar, Asnar (International Journal Labs, 2023)
Background: Backlog issues were the main problems during the pandemic. Samarinda City Government is trying to overcome this by presenting affordable housing with the concept of the welfare state (wohlfahrtsstaat). However, this has not been realized, especially for the homeless and People with Social Welfare Problems (PMKS). Aim: This study aims to analyze the Samarinda City Government’s effort to overcome the backlog issue to fulfill the right to decent housing for PMKS. Method: This research used a juridical normative method by statute and a case study approach with legal sociological. Findings: The results show the housing rights fulfillment in Samarinda City has not been fulfilled as a crucial issue to mitigate the spread of Covid-19. The policy implications are still in conflict with constraints such as land availability and are not yet equity-oriented. It is necessary to synchronize policy arrangements with the fulfillment of rights through human rights conventions which are ratified by the Samarinda City Government on availability, affordability, and sustainability aspects.